2004
DOI: 10.1007/s10725-004-4113-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of ornithine decarboxylase (ODC) gene family members in transgenic tobacco (Nicotiana tabacum L. cv. Bright Yellow 2) cell suspensions by methyl-jasmonate treatment

Abstract: Two nuclear genes (NtODC-1 and NtODC-2) encoding ornithine decarboxylase (ODC, EC 4.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(93 reference statements)
1
5
0
Order By: Relevance
“…Despite a substantial decrease in both ADC transcript levels and enzyme activity, only minor effects upon the capacity of N. tabacum to synthesize nicotine were observed (Chintapakorn and Hamill, 2007). Together with previous observations that showed ODC transcript levels and enzymatic activity were strongly up-regulated in plants in response to wounding, and also in cell and root cultures treated with methyl jasmonate (Mizusaki et al, 1973;Saunders and Bush, 1979;Imanishi et al, 1998;Wang et al, 2000;Xu et al, 2004;Cane et al, 2005), these results suggested that the presence of ODC in N. tabacum is essential for nicotine production, particularly in response to wound-associated stress. To test this suggestion experimentally, we have undertaken experiments to diminish ODC transcript levels in vivo and assess effects on alkaloid metabolism in tissues ± wound-associated stress.…”
Section: Introductionsupporting
confidence: 70%
“…Despite a substantial decrease in both ADC transcript levels and enzyme activity, only minor effects upon the capacity of N. tabacum to synthesize nicotine were observed (Chintapakorn and Hamill, 2007). Together with previous observations that showed ODC transcript levels and enzymatic activity were strongly up-regulated in plants in response to wounding, and also in cell and root cultures treated with methyl jasmonate (Mizusaki et al, 1973;Saunders and Bush, 1979;Imanishi et al, 1998;Wang et al, 2000;Xu et al, 2004;Cane et al, 2005), these results suggested that the presence of ODC in N. tabacum is essential for nicotine production, particularly in response to wound-associated stress. To test this suggestion experimentally, we have undertaken experiments to diminish ODC transcript levels in vivo and assess effects on alkaloid metabolism in tissues ± wound-associated stress.…”
Section: Introductionsupporting
confidence: 70%
“…Promoter analysis by PLACE indicated that the fragment has GCC-box homologs. The presence of a G-box motif was somehow expected considering that, along with the GCC-box (GCCGCC), they constitute the most common regulatory elements found in JA-responsive promoters (Kim et al 1992;Mason et al 1993;Guerineau et al 2003;Boter et al 2004;Xu et al 2004;De Boer et al 2011;Aviles-Arnaut and Delano-Frier 2012). Therefore, the fragment between −131 and −219 could be the JA-responsive element of the tasy gene, similar to the other promoters of JA-responsive genes.…”
Section: Discussionmentioning
confidence: 97%
“…To enhance detection sensitivity, a relatively moderate cuto score of 5.5 was employed. e computer-assisted search predicted three candidates sites (O1, O2, and O3) for tobacco ODC1 (Imanishi et al 1998), two sites (O4, and O5) for tobacco ODC2 (Xu et al 2004), one (A1) for tobacco A622 (Shoji et al 2002), and two (M1 and M2) for tobacco MATE1 (Shoji et al 2009). e enzyme genes of tropane alkaloids contained in their promoter regions two potential binding sites (AP1, and AP2) for Atropa belladonna PMT1 (Suzuki et al 1999b), one site (HT1) for Hyoscyamus niger TR-I (Nakajima et al 1999), two sites (AH1, and AH2) for A. belladonna H6H (Suzuki et al 1999a), and two sites (HH1, and HH2) for H. niger H6H (Kanegae et al 1994) (Figure 2A).…”
Section: Erf189-binding Sites In the Promoters Of Structural Genes Inmentioning
confidence: 99%